2001
DOI: 10.1152/ajpendo.2001.280.1.e120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperprolactinemia on rat prostate growth: evidence of androgeno-dependence

Abstract: The effects of the polypeptide hormone prolactin (PRL) in the development and regulation of benign prostate hyperplasia (BPH) and also in prostate cancer are not very well characterized. This study examines the action of PRL, either alone or in association with androgens [testosterone (T) or dihydrotestosterone (DHT)], in the rat prostate gland. The effects of PRL and androgens were investigated after 30 and 60 days in control, castrated, castrated with a substitutive implant of T or DHT, and sham-operated Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 66 publications
(88 reference statements)
10
82
1
5
Order By: Relevance
“…The demonstration by Van Coppenolle et al (30) that hyperprolactinemia is effective to induce prostate enlargement in castrated DHT-implanted animals is not contradicted by the present findings. Besides, augmenting the amount of prostatic DHT by increasing both 5a-R isozymes, PRL probably enhances the effects of DHT in this gland.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The demonstration by Van Coppenolle et al (30) that hyperprolactinemia is effective to induce prostate enlargement in castrated DHT-implanted animals is not contradicted by the present findings. Besides, augmenting the amount of prostatic DHT by increasing both 5a-R isozymes, PRL probably enhances the effects of DHT in this gland.…”
Section: Discussionsupporting
confidence: 60%
“…Chronic hyperprolactinemia was induced by daily intraperitoneal (i.p.) injections of 40 mg/kg aqueous sulpiride solution (Sigma) according to Van Coppenolle et al (30). The rats were always injected at 9:00 a.m. At 30 min, after the final injection, the rats were euthanized by decapitation to avoid possible adverse effects of anesthesia.…”
Section: Animalsmentioning
confidence: 99%
“…Similarly, dilation of the bulbourethral glandular acini or ducts, progressing to cystic atrophy may be observed in aging rats and mice where enlarged bulbourethral glands are often sampled as gross abnormalities (Kiupel, Brown, and Sundberg 2000;Wardrip et al 1998). Diffuse acinar or vesicle dilation due to increased secretory product and accompanied by organ weight increase has been reported as a druginduced finding, and has also been described with hyperprolactinemia and hyperandrogenism (Coert et al 1985;Van Coppenolle et al 2001). (Gordon, Majka, and Boorman 1996;Liu and Hurtt 1996;Stolte 1993;Sugimura, Cunha, and Donjacour 1986;Suwa et al 2002).…”
Section: Bulbourethral Glandmentioning
confidence: 99%
“…The released estrogens cause increased stimulation of the prostatic stroma, resulting in excessive proliferation of the prostate and occurrence of BPH (Krieg et al, 1995;Shibata et al, 2000). Indeed, it has been suggested that estrogen is a major risk factor of BPH (Seppelt, 1978;Van Coppenolle et al, 2001). Although the mechanism by which estrogen leads to the development of BPH has not been fully understood, available studies have shown that estrogen has direct and indirect effects at the cellular level on the prostate.…”
Section: Discussionmentioning
confidence: 99%